Perbandingan Latihan Plyometric dan Latihan Resistance Band Terhadap Power Otot Tungkai pada PS. Garuda Nusantara - Batra, Esty Wahyuni; Sutiyono, Bambang; Miftakhudin, Heru (Institut Nalanda, 2025)
This study aims to compare training using Plyometric and Resistance Band on leg muscle Power at PS. Garuda Nusantara. The design of this study is quantitative using Two Group Pretest-Posttest Design. Sampling using purposive as many as 14 athletes, divided into 2 groups. The treatment given was 16 meetings with a frequency of 3 times a week. Data processing using the t test with a significance level of 5%. The results of the study; based on the results of the initial test and the final test of Plyometric training, the calculated t = 5.25> t table 5% = 2.447, meaning that there is a significant difference between the mean of the initial test results and the final test results can be interpreted that Plyometric training can increase leg muscle Power. Based on the results of the initial test and the final test of Resistance Band training, the calculated t = 5.52> t table 5% = 2.447, meaning that there is an insignificant difference between the mean of the initial test results and the final test results can be interpreted that Resistance Band training can increase leg muscle Power. Comparison of the results of the final test of Plyometric exercise and the final test of Resistance Band exercise, the calculated t obtained was 0.746 smaller than the t table 5% = 2.179. This means that there is no significant difference between the mean data of the Plyometric exercise group and the Resistance Band exercise group.